Atopic dermatitis phenotypes and the need for personalized medicine. Issue 4 (August 2017) - Cabanillas, Beatriz; Brehler, Ann-Christin; Novak, Natalija
Abstract : Purpose of review: To describe recent developments in therapies which target the molecular mechanisms in atopic dermatitis. Recent findings: Current advances in the understanding of the molecular basis of atopic dermatitis are leading to the stratification of different atopic dermatitis phenotypes. New therapies offer the option to target-specific molecules involved in the pathophysiology of atopic dermatitis. Current new therapies under investigation aim to modulate specific inflammatory pathways associated with distinctive atopic dermatitis phenotypes, which would potentially translate into the development of personalized, targeted-specific treatments of atopic dermatitis. Summary: Despite the unmet need for well tolerated, effective, and personalized treatment of atopic dermatitis, the current standard treatments of atopic dermatitis do not focus on the individual pathogenesis of the disease. The development of targeted, phenotype-specific therapies has the potential to open a new promising era of individualized treatment of atopic dermatitis.